Towards more sustainable agricultural landscapes: Lessons from Northwestern Mexico and the Western Highlands of Guatemala (2020)
A systematic process for assessing progress toward landscape sustainability goals is developed and tested. Application of the approach builds capacity and promotes continual improvements in management practices, thus enabling timely action to address changing conditions while progressing toward locally defined goals. We consider how the approach applies to agricultural landscapes, that is farm ecosystem interactions with the environment and human well-being. We present lessons learned from applying the assessment approach in two contrasting situations: large, high-input, commercial agriculture in northwestern Mexico and small, low-input family farms in the Western Highlands of Guatemala. Applying the approach reveals five attributes required for success and the means to achieve those conditions. (1) Having a capable local champion for the project is critical. (2) Implementation of the approach must be in concert with local people and organizations as well as with regional and national policies and programs. (3) Identification and engagement of key stakeholders is essential. (4) Application of the approach is not meant to be a one-time effort but rather an ongoing and systematic process. (5) Engagement and buy-in from stakeholders including multiple agency levels is essential for allocation of necessary resources and logistic support in the continuing implementation of the approach.